Resíduos orgânicos como fonte nitrogenada: impacto no desenvolvimento do feijoeiro e na fauna edáfica - Feltes, Janine Diéle (2023)
Pig farming and poultry farming stand out among the main activities developed in Rio Grande do Sul (RS). These increasingly intensive production systems generate large amounts of organic waste that have potential use as a source of nutrients for agricultural crops of economic interest. The objective of this work was to evaluate the impact of the use of organic and mineral nitrogen sources on common bean and edaphic fauna. The work was developed in the experimental area of the Department of Agronomic and Environmental Sciences of the Federal University of Santa Maria (UFSM), Campus Frederico Westphalen-RS. The experimental design was in randomized blocks with seven treatments and seven replications. The treatments consisted of alternative organic sources of N for the development of black bean: poultry litter (CA), swine liquid slurry (DLS) and a mineral spring (M), where T: control (without N application); CA: 100% of N via CA; CA+M: 50% of N via CA + 50% via mineral; DLS: 100% of N via DLS; DLS+M: 50% of N via DLS + 50% via mineral; CA+DLS: 50% of N via CA + 50% via DLS; and, M: 100% of N via mineral. It was observed that the treatments with the addition of N showed statistical difference for the plant growth and productivity variables, and the yield variables did not differ from each other. The edaphic fauna collections were carried out in four repetitions, in the period of pre-sowing, flowering and post-harvest of the bean plant with traps of the PROVID type. The use of DLS and CA associated with a mineral source proved to be efficient as a N management strategy in the crop, with increases in productivity in relation to mineral management and the control. The isolated application of DLS or associated with CA proved to be efficient for increasing productivity. The edaphic fauna is influenced by organic residues. The isolated application of DLS resulted in a decrease in abundance with a more expressive effect on the Collembola group, represented mainly by the Entomobrydae family, while treatments with CA provided an increase in abundance. The combined use of CA+DLS resulted in greater diversity and uniformity of distribution of edaphic fauna organisms.